Decoupled erosion of amphibians' phylogenetic and functional diversity due to extinction. Issue 2 (12th November 2019) - Oliveira, Brunno F.; Sheffers, Brett R.; Costa, Gabriel C.
Abstract: Aim: It has been argued that the loss of phylogenetic diversity (PD) from species extinctions will result in concomitant loss of functional diversity (FD). As a result, species extinction undermines not only unique evolutionary history, but also ecosystem function and stability. Using data from > 6, 000 amphibian species globally, we assess the potential erosion of PD and FD as a result of extinction. Location: Global. Time period: From the present day to the next 100 years. Major taxa studied: Amphibians (Anura, Caudata and Gymnophiona). Methods: We simulated future biogeographical patterns of extinction based on International Union for Conservation of Nature (IUCN) threat status, and estimated the loss of PD and FD accordingly. We used null models to determine the extent to which extinctions may result in disproportional losses of PD and FD relative to random extinction. Using spatial regressions, we tested whether the loss of PD can predict the loss of FD. Results: Although spatial patterns of current amphibian PD and FD were similar, extinctions did not retain this similarity. The magnitude of such a decoupling varied widely in space, with most of the global assemblages losing more FD than PD. Main conclusion: This study challenges the assumption that extinctions should yield comparable loss of PD and FD. Species may not be equivalent in the amount of unique evolutionary history and ecological functions that would be lost if they become extinct. Designing conservation strategies based on a single dimension of biodiversity has the danger of leading to misinformed outcomes.